Numerical simulations of realistic waves - Lek, Yi Rong (2016)
This report summarises the results of numerical simulation on the experiment of the floating wind turbine in dynamic rigid body model, using OpenFOAM software. A full domain simulation of the floating structure is modelled by OpenFOAM in dynamic rigid body model with 6 degree of freedom that includes Surge, Sway, Heave, Pitch, Roll and Yaw, and also with hydrodynamic solver modelled by Navier-stokes equation. In this numerical simulation, ihFOAM and interDyMFoam are used as solvers. InterDyMFoam is an enhanced version of interFoam which deals with dynamic meshes and uses the same governing equations to solve fluid motion. ihFOAM is an additional solver based on interFoam which has built in boundary conditions for wave generation and wave absorption. The capabilities of generating waves based on multiple wave theories and wave absorption have been used based on extrapolated two-dimensional theory which allows the waves to travel away with minor reflection. The floating structure was simulated with several different wave conditions. These simulations covered areas which include regular waves with different wave height, wave period and directions. Based on the findings of this project, it has contributed to the development and understanding of floating structure through the OpenFOAM simulation. The simulation can provide important details of the wave’s load acting on the structure and also the response of the structure in order to construct a reliable, cost-effective and high efficient floating structure.